Anthropometric measurement - An easy approach for evaluation of obesity (Bangladesh Medical Journal, 2014)
Now a days obesity is a burden worldwide. The prevalence of obesity is increasing in both the developed and developing countries. To investigate the anthropometric measurement in obesity. This cross study was carried out in the Department of Physiology, Mymensingh Medical College, Mymensingh, Bangladesh. Inclusion and exclusion criteria are strictly maintained for selection of study and control groups. Anthropometric measurements were performed in 150 cases of overweight and obese. BMI, WC, WHR, blood pressure were high in obese group. Obesity affects various anthropometric measurements and may be used to routinely evaluate obese patients. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18976 Bangladesh Med J. 2013 Jan; 42 (1): 25-27